2020
DOI: 10.1097/pas.0000000000001642
|View full text |Cite
|
Sign up to set email alerts
|

Gross Specimen Handling Procedures Do Not Impact the Occurrence of Spread Through Air Spaces (STAS) in Lung Cancer

Abstract: Spread Through Air Spaces (STAS) is a form of invasion characterized by neoplastic cell dissemination in the lung parenchyma surrounding the outer edge of the tumor. Its possible artifactual origin is widely debated in the literature. The aim of this study is to investigate the potential impact of gross sampling procedures in causing STAS. A prospective series of 51 surgical lung specimens was collected (35 adenocarcinomas, 68.6%; 13 squamous cell carcinomas, 25.5%; 2 large-cell neuroendocrine carcinomas, 3.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…However, some scholars have questioned STAS, arguing that it is only the spread of tumor cell clusters caused by knife cutting during specimen processing, and called it "Spread Through a Knife Surface" [ 12 ]. Recently, more and more studies have shown that STAS is an in vivo phenomenon rather than an artifact caused by specimen handling procedures [ 13 , 23 , 24 ]. However, could this in vivo phenomenon be another manipulation artifacts, caused by preoperative invasive biopsy?…”
Section: Discussionmentioning
confidence: 99%
“…However, some scholars have questioned STAS, arguing that it is only the spread of tumor cell clusters caused by knife cutting during specimen processing, and called it "Spread Through a Knife Surface" [ 12 ]. Recently, more and more studies have shown that STAS is an in vivo phenomenon rather than an artifact caused by specimen handling procedures [ 13 , 23 , 24 ]. However, could this in vivo phenomenon be another manipulation artifacts, caused by preoperative invasive biopsy?…”
Section: Discussionmentioning
confidence: 99%
“…62 The occurrence of STAS does not seem to be affected by gross specimen-handling procedures. 63 STAS in adenocarcinoma is composed of three morphologic patterns, including micropapillary structures, solid nests, and discohesive single cells. 61 STAS is associated with worse clinical outcome in resected lung adenocarcinoma and all investigated major histologic lung cancer types.…”
Section: Grading Of Invasive Nonmucinous Adenocarcinomamentioning
confidence: 99%
“…1,23 Furthermore, a recent series demonstrated that gross specimen handling procedures did not impact the incidence of STAS in lung carcinoma specimens, suggesting that STAS is not a pathologist induced artifact from knife translocation of tumor cells. 24 While concerns have been raised that individual STAS clusters can survive in the airway separate from the tumor, our observations that viable STAS cells, with no evidence of necrosis, in additional resection specimens up to 1 month after the initial procedure confirms that cell clusters can survive distant from the tumor. Whether the spread of tumor cells is introduced by surgical manipulation of the tumor at the time of surgery has also been questioned.…”
Section: Discussionmentioning
confidence: 51%